Hierarchical Surface Texturing of Hydroxyapatite Ceramics: Influence on the Adhesive Bonding Strength of Polymeric Polycaprolactone - Biggemann, Jonas; Müller, Philipp; Köllner, David; Simon, Swantje; Hoffmann, Patrizia; Heik, Paula; Lee, Jung Heon; Fey, Tobias (Journal of Functional Biomaterials, 2020)
The tailored manipulation of ceramic surfaces gained recent interest to optimize the performance and lifetime of composite materials used as implants. In this work, a hierarchical surface texturing of hydroxyapatite (HAp) ceramics was developed to improve the poor adhesive bonding strength in hydroxyapatite and polycaprolactone (HAp/PCL) composites. Four different types of periodic surface morphologies (grooves, cylindric pits, linear waves and Gaussian hills) were realized by a ceramic micro-transfer molding technique in the submillimeter range. A subsequent surface roughening and functionalization on a micron to nanometer scale was obtained by two different etchings with hydrochloric and tartaric acid. An ensuing silane coupling with 3-aminopropyltriethoxysilane (APTES) enhanced the chemical adhesion between the HAp surface and PCL on the nanometer scale by the formation of dipole–dipole interactions and covalent bonds. The adhesive bonding strengths of the individual and combined surface texturings were investigated by performing single-lap compressive shear tests. All individual texturing types (macro, micro and nano) showed significantly improved HAp/PCL interface strengths compared to the non-textured HAp reference, based on an enhanced mechanical, physical and chemical adhesion. The independent effect mechanisms allow the deliberately hierarchical combination of all texturing types without negative influences. The hierarchical surface-textured HAp showed a 6.5 times higher adhesive bonding strength (7.7 ± 1.5 MPa) than the non-textured reference, proving that surface texturing is an attractive method to optimize the component adhesion in composites for potential medical implants.
Keywords: hierarchical surface texturing; surface functionalization; hydroxyapatite; polycaprolactone; acid etching; tartaric acid; silane; adhesive bonding strength